Ecological Agriculture in Southern Brazil: From Alternative to Counter-Tendency - Flávia Charão Marques; Daniela Oliveira (Íconos)
This article presents some reflections about the socio-technical changes in agriculture understood as counter-movements to development strategies based on modernization. By examining the emblematic case of Ipê-Antônio Prado in the far south of Brazil, this study confirms that through the collaboration of various actors new productive practices, discourses, performances and multiple social processes emerge that reposition local forms of organization. The study identifies the emergence of an endogenous expression of ‘ecological agriculture’ that was initiated within the broader framework of alternative agriculture. However this shift has triggered heterogeneous courses of action in the region that have configured new processes of change for agricultural production.